Learning & Working in a Co-operative Virtual Environment - Catasús, Montse Guitert; Prado, Ferran Giménez; Grau, Teresa Lloret (Proceedings of the International Conference on Networked Learning, 2002)
One of the basic present education challenges is to prepare people to be able to participate in an information society in which knowledge is the critical source of social and economic development. In this society, productive collaboration is the key issue of interactive organization networks that are open to constant changes.